Descriptive Memoir of Planning Commission. - Planning Commission (Planning Commission, 1954)
The Planning Commission, established by the Government of India in March 1950, functioned as an advisory body tasked with the formulation and oversight of the country’s national plans, most notably the First Five Year Plan (1951-52 to 1955-56). Its core functions included assessing the country’s material, capital, and human resources, formulating strategies for their effective utilization, prioritizing development stages, proposing resource allocations, and monitoring progress with recommendations for policy adjustments. The Commission worked closely with both Central and State Governments, with decision-making and implementation resting with them, while also coordinating through the National Development Council, which included the Prime Minister, Chief Ministers, and Commission members to ensure balanced national development. Organisationally, the Commission comprised a Secretariat divided into administrative, coordination, and public co-operation branches, along with eight technical divisions focusing on resources, finance, industry, agriculture, social services, land reforms, and overall progress. A Research Programmes Committee facilitated studies on social, economic, and administrative challenges, while the Programme Evaluation Organisation, supported by the Ford Foundation, undertook systematic assessment of community development projects to provide insights into policy effectiveness and programme impact. The Planning Commission thus combined advisory, research, coordination, and evaluative functions to guide India’s post-independence development strategy and strengthen the implementation of national plans across diverse sectors and regions.
Government of India, Cabinet Secretariat (O. and M. Division)
Government of India, Cabinet Secretariat (O. and M. Division)
Keywords: Five Year Plan, National Development Council, Resource Assessment, Policy Coordination, Programme Evaluation Organisation, Community Development, Economic Planning, Advisory Body, Research Programmes, Secretariat Organisation, Central and State Governments